Phytochemical and in vitro Screening of Justicia spicigera Ethanol Extract for Antioxidant Activity and in vivo Assessment Against Schistosoma mansoni Infection in Mice - Awad, Nagwa E.; Abdelkawy, Mostafa A.; Abdelrahman, Enas H.; Hamed, Manal A.; Ramadan, Nehal S. (Anti-Infective Agents, 2018)
Background: Chemotherapy of schistosomiasis by certain drugs is impractical due to the resistance of Schistosoma larvae to schistosomiasis drugs after long treatment period. The aim of this work is to monitor Schistosoma mansoni infection on mice livers after treatment with the ethanolic extract of Justicia spicigera areal parts and the herbal antishistosomal drug (Mirazid); the oleo-resin extract from Myrrh of Commiphora molmol tree. Methods: Liver function enzymes; Aspartate Aminotransferase (AST); Alanine Aminotransferase (ALT), Alkaline Phosphatase (ALP), Gamma Glutamyl Trans- Peptidase (GGT) and serum total protein content were estimated. Oxidative stress markers; Malondialdehyde (MDA), Glutathione (GSH) and Super Oxide Dismutase (SOD) were also evaluated. Parasitological and histopathological studies through numbers of worm burden and liver pathology pattern were done. Results: The results showed obvious decreases in AST, ALT, ALP, GGT, total protein, MDA and SOD after treatment with plant extract or the selected drug, while GSH recorded significant increase after treatment. A noticeable decrease in worm count and an improvement in histopathological picture of the infected mice liver were detected. Conclusion: The ethanolic extract of Justicia spicigera areal parts recorded antioxidants and antischistosomal effects. Further work is needed to validate its safety and for considering it as anti-schisotosomal drug.
Keywords: schistosomiasis